2014
DOI: 10.1177/0218492314536568
|View full text |Cite
|
Sign up to set email alerts
|

Repair of congenital heart defects associated with single pulmonary artery

Abstract: Complete repair of congenital heart defects in patients with unilateral absence of a pulmonary artery is associated with a relatively low risk. If the hilar artery is of adequate size, surgical intervention should attempt restoration of the communication between the disconnected hilar artery and the pulmonary trunk, in addition to repairing the heart defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Bockeria, L. A. et al [26] concluded a result of hospital mortality of 5% in 37 patients, they suggested the NI and NI Z-score should be greater than 200 mm 2 /m 2 and -4 for a successful complete repair, or palliative intervention was required. Yang, T. et al [27] reported a good follow-up results with no deaths in 17 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bockeria, L. A. et al [26] concluded a result of hospital mortality of 5% in 37 patients, they suggested the NI and NI Z-score should be greater than 200 mm 2 /m 2 and -4 for a successful complete repair, or palliative intervention was required. Yang, T. et al [27] reported a good follow-up results with no deaths in 17 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The NI and McGoon ratio meet the criterion which the previous study prescribed. [26] The primary correction was performed with the revascularization of the affected PA. Only one patient with a lower NI and McGoon ratio occurred pulmonary hemorrhage after surgery (Patient No.4).…”
Section: Discussionmentioning
confidence: 99%